Distributed Coordination of Multi-agent Networks Emergent Problems, Models, and Issues - Ren, Wei.; Cao, Yongcan (2011)
Multi-agent systems have numerous civilian, homeland security, and military applications; however, for all these applications, communication bandwidth, sensing range, power constraints, and stealth requirements preclude centralized command and control. The alternative is distributed coordination, which is more promising in terms of scalability, robustness, and flexibility.Distributed Coordination of Multi-agent Networks introduces problems, models, and issues such as collective periodic motion coordination, collective tracking with a dynamic leader, and containment control with multiple leaders, and explores ideas for their solution. Solving these problems extends the existing application domains of multi-agent networks; for example, collective periodic motion coordination is appropriate for applications involving repetitive movements, collective tracking guarantees tracking of a dynamic leader by multiple followers in the presence of reduced interaction and partial measurements, and containment control enables maneuvering of multiple followers by multiple leaders.The authors' models for distributed coordination arise from physical constraints and the complex environments in which multi-agent systems operate; they include Lagrangian models - more realistic for mechanical-systems modeling than point models - and fractional-order systems which better represent the consequences of environmental complexity.Other issues addressed in the text include the time delays inherent in networked systems, optimality concerns associated with the deisgn of energy-efficent algorithms, and the use of sampled-data settings in systems with intermittent neightbor-neighbor contact. Researchers, graduate students, and engineers interested in the field of multi-agent systems will find this monograph useful in introducing them to presently emerging research directions and problems in distributed coordination of multi-agent networks.
Part I: Preliminaries and Literature Review -- Preliminaries -- Overview of Recent Research in Distributed Multi-agent Coordination -- Part II: Emergent Problems in Distributed Multi-agent Coordination -- Collective Periodic Motion Coordination -- Collective Tracking with a Dynamic Leader -- Containment Control with Multiple Leaders -- Part III: Emergent Models in Distributed Multi-agent Coordination -- Networked Lagrangian Systems -- Networked Fractional-order Systems -- Part IV Emergent Issues in Distributed Multi-agent Coordination -- Sampled-data Setting -- Optimality Aspect -- Time Delay.
Keywords: Engineering; Artificial intelligence; Engineering; Control; Artificial Intelligence (incl. Robotics).; ROBOTICS AND AUROMATION; COMMUNICATIONS ENGINEERING, NETWORKS; SYSTEMS THEORY; TELECOMUNICACIÓN